Zoorkhane and Its Identification Resources - sina amini zadeh; daryoush boustani (توسعه اجتماعی)
The aims of this study is qualitative investigation of the sport of Zoorkhaneh by an emic and interpretive approach. 15 members of the Kerman's Zoorkhaneh were participated in this research. Four categories were extracted by using qualitative methodology of Grounded Theory. They are, instruments of the Zoorkhaneh: art and architecture; poems and ceremonies; and characters. Generally, finding indicated that: sport of the Zoorkhaneh has a heavy influence on formation of the heroic (Pahlevani) Identity. Actually, the heroic (Pahlevani) identity is being constructed by ceremonies, sport practices and method of practicing and working by instruments of the Zoorkhaneh accompanied by epic and religious poems. In fact instruments of the Zoorkhaneh, kind of the poem that called out, traditional architecture, and presence of the epic and religious characters of past and contemporary such as Takhti and Pouria-y-Vali, complement each other. This process increases the influence of Zoorkhaneh on identity formation and culminated in formation of a unique identity as the heroic (Pahlevani) identity.